Study of the Pharmacokinetics and Safety of Dioxidine®, Solution for Topical and External Use, 0.25 mg/ml, in Various Routes of Administration - V. A. Stepanov; S. V. Ponasenkova; E. S. Simonova; P. D. Sobolev; A. G. Nikiforova; A. A. Globenko; A. V. Kapashin; M. A. Pasko (Антибиотики и Химиотерапия)
Topical use of antibacterial drugs as part of complex therapy for purulent-inflammatory infections of the skin and oropharynx can not only eliminate the symptoms but also influence the cause of the disease. Dioxidine® is a broad-spectrum antibacterial drug, active against both gram-positive and gram-negative bacteria. The aim of this study was to investigate the bioavailability, pharmacokinetic parameters, and safety profile of Dioxidine®, solution for topical and external use, 0.25 mg/ml, in cutaneous and topical application. Another dosage form of Dioxidine® — a solution for infusion and external use, 5 mg/ml — was used as a comparison drug. The study consisted of 4 stages reflecting different routes of drug administration: rinsing the oropharynx (path A), a single irrigation of the oropharynx using a spray nozzle (path B), back skin irrigation (path C), and intravenous administration (path D — for the reference drug). The results of the study made it possible to determine the absolute dose-normalized bioavailability of the study drug in the indicated routes of administration, as well as to evaluate its safety profile.